Wanita karir dalam fiqh munakahah: Menyeimbangkan peran antara pekerjaan dan keluarga - Rahmadani, Karina Aning (Maliki Interdisciplinary Journal, 2024)
This article discusses the role of career women in the context of fiqh munakahah, which regulates the relationship between husband and wife in the household. In the modern era, women not only take care of the household but are also active in the world of work, which requires wives to balance their responsibilities at work and at home. This phenomenon brings its own challenges for career women, especially in fulfilling social and cultural expectations that often place women in the traditional position as housekeepers. From the perspective of fiqh munakahah, career women have the right to work and develop their careers but are also expected to fulfill their roles as wives and mothers. This article will explore the rights and obligations that career women have within the principles of fiqh munakahah, as well as the challenges they face in balancing both roles. As well as the need for support from a husband in order to achieve the desired balance.